OS SUBSUNÇORES DO ATLETISMO NA APRENDIZAGEM SIGNIFICATIVA DE ESCOLARES DO ENSINO MÉDIO (Fiep Bulletin - online, 2024)
Introduction: Meaningful learning occurs through anchoring or learning subsumers that relate new knowledge to the student's prior knowledge. Regarding subordinate learning, new information from Physical Education, Mathematics and Physics acquires meaning when it interacts with the subsumers – hide-and-seek, addition, speed – and the new material is subordinated to the cognitive structure. Objective: Promote and analyze meaningful learning through interdisciplinarity between the disciplines Physical Education, Mathematics and Physics, using prior knowledge as a basis for substantial and enjoyable learning. Methods: The research is configured as action research approved by the Research Ethics Committee of the State University of Amazonas- BR, under number: 5,608,528, based on an experimental design, under an empirical-analytical focus and mixed approach, with statistical and content analysis, applied experimentally in 160 students from the four 1st grade classes of the New High School participated in the research, divided into groups of 10 students from each class, Physics, Mathematics and Physical Education teachers from the Garcitylzo do Lago e Silva full-time school. Results: The application of interdisciplinarity in the disciplines involved, in general, helped with the results of students' grades at that school. Conclusion: The subsumers applied to interdisciplinarity between subjects such as Physical Education, Mathematics and Physics can facilitate meaningful learning, allowing students to relate the concepts learned with their practical experiences. There was a significant improvement in the students' academic performance, in addition to high knowledge in the three areas of knowledge, namely: Physical Education, Physics and Mathematics.